Processing GOTO survey data with the Rubin Observatory LSST Science Pipelines II: Forced Photometry and lightcurves. (4th June 2021) - Makrygianni, L.; Mullaney, J.; Dhillon, V.; Littlefair, S.; Ackley, K.; Dyer, M. J.; Lyman, J.; Ulaczyk, K.; Cutter, R.; Mong, Y.-L.; Steeghs, D.; Galloway, D. K.; et al.
Abstract: We have adapted the Vera C. Rubin Observatory Legacy Survey of Space and Time (LSST) Science Pipelines to process data from the Gravitational-wave Optical Transient Observer (GOTO) prototype. In this paper, we describe how we used the LSST Science Pipelines to conduct forced photometry measurements on nightly GOTO data. By comparing the photometry measurements of sources taken on multiple nights, we find that the precision of our photometry is typically better than 20 mmag for sources brighter than 16 mag. We also compare our photometry measurements against colour-corrected Panoramic Survey Telescope and Rapid Response System photometry and find that the two agree to within 10 mmag (1 σ ) for bright (i.e., 14th mag ) sources to 200 mmag for faint (i.e., 18th mag ) sources. Additionally, we compare our results to those obtained by GOTO's own in-house pipeline, gotophoto, and obtain similar results. Based on repeatability measurements, we measure a 5σ L -band survey depth of between 19 and 20 magnitudes, depending on observing conditions. We assess, using repeated observations of non-varying standard Sloan Digital Sky Survey stars, the accuracy of our uncertainties, which we find are typically overestimated by roughly a factor of two for bright sources (i.e., < 15th mag ), but slightly underestimated (by roughly a factor of 1.25) for fainter sources ( > 17th mag ). Finally, we present lightcurves for a selection of variable sources and compare them to those obtained with the Zwicky Transient Factory and GAIA. Despite the LSST Software Pipelines still undergoing active development, our results show that they are already delivering robust forced photometry measurements from GOTO data.